Analysis of Non-Linguistic Obstacles in Learning Arabic Speaking Skills at Khairunnas Islamic Senior High School, Surabaya - Primasti Nur Yusrin Hidayanti; Siti Alfi Aliyah; Nabila Nailil Amalia; Mirwan Akhmad Taufiq; Maturedy, Faris; Mohammed Jassim Mohammed Rady (Arabiyatuna: Jurnal Bahasa Arab, 2025)
The learning of maharah kalam (Arabic speaking skills) at Khairunnas Islamic Senior High School, Surabaya, encountered several non-linguistic obstacles that hindered students’ speaking proficiency. This study aimed to identify and analyze these barriers and propose relevant pedagogical solutions. A descriptive qualitative approach was employed, involving one teacher and eight twelfth-grade Science students as participants. Data were collected through observation, interviews, and questionnaires, and analyzed through data reduction, data display, and verification using source triangulation. The findings revealed three categories of non-linguistic barriers: (1) psychological factors, such as low motivation and self-confidence; (2) pedagogical factors, including monotonous teaching methods and limited speaking practice; and (3) socio-academic factors, particularly the lack of a school environment that supports the active use of Arabic. The study concludes that implementing communicative teaching methods and fostering a supportive language environment are essential to improving students’ Arabic speaking skills.